Polyolefin graft copolymers through a ring-opening metathesis grafting through approach. Issue 14 (15th March 2021) - Wang, Huiqun; Onbulak, Sebla; Weigand, Steven; Bates, Frank S.; Hillmyer, Marc A.
Abstract : A series of polyethylene- g -atactic polypropylene graft copolymers were synthesized by grafting through copolymerization of a cyclooctene terminated aPP macromonomer with cyclooctene monomer and subsequent hydrogenation. Abstract : A series of polyethylene- graft -atactic polypropylene (PE- g -aPP) graft copolymers were synthesized by grafting through copolymerization of a cyclooctene terminated aPP macromonomer and cyclooctene using ring opening metathesis polymerization (ROMP) and subsequent hydrogenation. The macromonomer was prepared by a facile alkoxycarbonylation reaction between 1, 5-cycooctadiene, hydroxyl terminated aPP and carbon monoxide (CO). Near complete monomer conversion, a near random graft distribution, and relatively low dispersity ( Đ < 2.0) were achieved. Thermal analysis of the graft polymers indicates decreasing melting temperatures ( T m ) and glass transition temperatures ( T g ) as the weight percentage of aPP ( W PP ) increases. The percent crystallinity ( X c ) of PE decreases as aPP content increases, confirmed by differential scanning calorimetry (DSC) and wide angle X-ray scattering (WAXS) charaterization. The normalized percent crystallinity ( X c, norm ) indicates that changing side chain numbers and/or length of aPP do not have a significant impact on PE crystallinity. Small angle X-ray scattering (SAXS) indicates the PE lamellae crystals in the graft copolymers have similar interlamellar spacing but decreased thickness as aPP content increases. In addition, the linear viscoelastic behavior shows that the PE- g -aPP graft copolymers exhibit greatly enhanced dynamic modulus and complex viscosity compared to the linear PE, and the effect increases as side chain number and/or length increases. This work is important for further development of such graft polymers for direct recycling of ubiquitous polyolefins from mixed polyolefin waste.